Study on Properties Influence of Carbon Fiber-reinforced Polyimide Composites using Melamine as a Crosslinking Agent - Shiediqque, Apang Djafar; Widarman, Agung; Suriaman, Irwan; Zahra, Ghefira Iftina; Maesaroh, Kiki; Edwin, Rudiawan; Laksmono, Joddy Arya (Universitas Jenderal Soedirman, 2025)
ABSTRACT: Advances in carbon fiber reinforced polymer (CFRP) technology remain critical, particularly in meeting the demand for lightweight and durable materials in the transportation industry. With the advent of electric vehicles (EVs), there is a pressing need for composite materials that offer not only exceptional mechanical strength but also high-temperature stability and heat resistance. Polyimide, known for its excellent heat resistance and flame retardancy properties, is an optimal choice for developing such composites. Furthermore, the incorporation of melamine as a crosslinker in polyimide has been shown to significantly enhance its performance. Our study involved the production of a carbon fiber reinforced composite with a melamine crosslinked polyimide matrix (CFMPI), to meet these critical requirements. The composite showed a tensile strength of 84.17 MPa, a tensile modulus of 1899.14 MPa at 1.5% mole substitution of 4,4’‑oxydianiline by melamine as a crosslinker for polyimide with thermal stability up to 562 °C. These results indicated that this composite material is highly suitable for use in EVs. Keywords: advanced composites, carbon fiber reinforced polymer, lightweight materials, melamine-crosslinker, polyimide composites.